DaiTongXiao improves gout nephropathy by inhibiting inflammatory response through the TLR4/MyD88/NF-κB pathway - Liu, Feifan; Bai, Yuanmei; Wan, Yan; Luo, Shifang; Zhang, Linao; Wu, Xue; Chen, Rong; Yin, Zili; Xie, Yuhuan; Guo, Peixin (Frontiers in Pharmacology, 2024)
Gouty nephropathy (GN) arises from factors like excessive purine intake, metabolic disorder, or abnormal synthesis, and uric acid hyper-saturation in blood, leading to urate crystals deposition in kidney tissue. Daitongxiao (DTX) is a remedy used by Dai people of China, shows efficacy in lowering uric acid levels and exhibits anti-inflammatory and kidney protective properties. A GN rat model was induced using adenine and potassium oxonate. Following DTX administration, various parameters were assessed in urine, serum, and kidney tissue. Western blot analysis evaluated TLR4/MyD88/NF-κB signaling proteins, while immunofluorescence examined NF-κB nuclear expression. DTX treatment improve kidney morphology, increased body weight and kidney index, and enhanced urinary levels of blood urea nitrogen (Bun), 24h urinary protein, uric acid (UA), and allantoin in GN rats, reducing UA, Bun, creatinine (Cre), Cystatin C (CysC), Serumamyloid A (SAA), α1-microglobulin (MG) and β2-MG in serum analysis. Renal tissue assessments showed decreased Xanthine oxidase (XOD), Hydroxyproline (Hyp), α-smooth muscle actin (α-SMA) and Collage TypeⅣ (COL-Ⅳ). Kidney damage severity was notably reduced. DTX lowered serum inflammatory factors interleukin (IL) -18, tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), transforming growth factor-β1 (TGF-β1), IL-1β in rat serum, reducing chemokine Monocyte chemoattractant protein-1 (MCP-1) and adhesion factor vascular cell adhesion molecule-1(VCAM-1). Western blotting demonstrated downregulation of TLR4/MyD88/NF-κB pathway proteins, and immunofluorescence revealed reduced NF-κB expression in renal tissue. DTX exhibits significant anti-GN effects by modulating TLR4/MyD88/NF-κB pathway protein expression, reducing inflammatory factor release, and inhibiting GN progression.